ANALISIS KUALITAS AIR PADA SUMBER MATA AIR DI KECAMATAN KARANGAN DAN KALIORANG KABUPATEN KUTAI TIMUR - Iin Sumbada Sulistyorini; Muli Edwin; Adriana Sampe Arung (Jurnal Hutan Tropis, 2016)
The purpose of this study was to determine the water quality based on some parameters of physical, chemical and biological properties of the three springs. One location site in the district of Kaliorang and then two location site in the District of Karangan. Landscape characteristics in the two districts almost equal in the hills with a small incision. Likewise, the third location of water sources is a hilly area of karst (limestone). Karst landscapes not only provide material goods, biodiversity, but also providers of ecosystem services such as clean water, the water regulator and the potential of the upper and lower surfaces such as caves. The results showed that the physical quality of water from the three water sources meet the quality standards required. From the results of laboratory testing, chemical water quality at three locations contain BOD (Biochemical Oxygen Demand) and COD (Chemical Oxygen Demand) is relatively high. The high value of BOD and COD indicated that the water conditions have polluted by the accumulation of organic materials, especially the litter of the forest vegetation. Furthermore, for total coliform and fecal coliform although the amount is below the threshold quality standards required, but its existence in the water indicates the contamination of water sources by sewage as from agricultural run-off, animal feces containing the bacteria, viruses, or disease-causing organisms more, Based on the designated class of water, the springs at the third location is very suitable for use as irrigation, facilities or infrastructure freshwater fish farming, recreation, and other designation that requires the same quality standards. As for the water designation for drinking water must through the processing or specific treatment.Tujuan penelitian ini adalah untuk mengetahui kualitas air berdasarkan beberapa parameter fisik, kimia dan biologi dari tiga sumber mata air, yaitu satu lokasi di kecamatan Kaliorang dan dua lokasi di Kecamatan Karangan.Karakteristik bentang alam di dua kecamatan hampir sama, yaitu merupakan perbukitan dengan torehan kecil. Begitu juga ketiga lokasi sumber air merupakan kawasan perbukitan Karst (Batu kapur). Bentang lahan Karst bukan hanya menyediakan bahan-bahan material, keanekaragaman hayati, tetapi juga penyedia jasa ekosistem seperti air bersih, pengatur tata air dan potensi atas dan bawah permukaan seperti gua-gua. Hasil penelitian menunjukkan bahwa kualitas fisik air dari ketiga sumber air memenuhi baku mutu yang dipersyaratkan. Dari hasil pengujian laboratorium, kualitas kimia air di tiga lokasi memiliki kandungan BOD (Biochemical Oxygen Demand)  dan COD (Chemical Oxygen Demand) yang relatif tinggi. Tingginya nilai BOD dan COD mengindikasikan bahwa air tersebutt dalam kondisi tercemar oleh akumulasi bahan organik terutama seresah dari vegetasi hutan diatasnya. Selanjutnya untukTotal coliform dan Fecal coliform walaupun jumlahnya di bawah ambang batas baku mutu yang dipersyaratkan, namun keberadaaannya di dalam air menunjukkan adanya kontaminasi sumber mata air oleh limbah seperti dari limpasan pertanian, kotoran hewan yang mengandung bakteri, virus, dan atau organisme penyebab penyakit lainnya. Berdasarkan kelas peruntukkan air, sumber air di ketiga lokasi sangat sesuai untuk digunakan sebagai irigasi, sarana atau prasarana budidaya ikan air tawar, rekreasi, dan peruntukkan lainnya yang mempersyaratkan baku mutu yang sama. Sedangkan untuk peruntukkan air sebagai bahan baku air minum terlebih dahulu harus melalui pengolahan atau treatment tertentu.